EWS/FLI1 Target Genes and Therapeutic Opportunities in Ewing Sarcoma - Cidre-Aranaz, Florencia; Alonso, Javier (Frontiers in Oncology, 2015)
Ewing sarcoma family of tumors are aggressive bone malignancies that affect children and young adults. Ewing sarcoma is the second most common primary bone malignancy in pediatric patients. Although significant progress has been made in the treatment of Ewing sarcoma since it was first described in the 1920s, in the last decade survival rates have remained unacceptably invariable, thus pointing to the need of new approaches centered in the molecular basis of the disease. Ewing sarcoma driving mutation, EWS-FLI1, which results from a chromosomal translocation, encodes an aberrant transcription factor. Since its first characterization in the 1990’s, many molecular targets have been described to be regulated by this chimeric transcription factor. Their contribution to orchestrate Ewing sarcoma phenotype has been reported over the last decades. In this work we will focus on the description of a selection of EWS/FLI1 targets, their functional role and their potential clinical relevance. We will also discuss their role in other types of cancer as well as the need for further studies to be performed in order to achieve a broader understanding of their particular contribution to Ewing sarcoma development.